Domestic Policies and Foreign Resource Requirements - Quibria, M. G. (Quarterly Journal of Economics, 1981)
The paper argues that appropriate domestic policies — more particularly, the real wage policy that is stressed here — can reduce the extent of foreign dependence of a country. It shows that foreign aid sufficient to achieve a given level of per capita domestic income is positively related to the real wages in an LDC with unemployment. The paper also links the level of real wages and the rate of technical change to the possibilities for self-sufficiency (from foreign aid) in the long run.